Effect of the coexistence of CO2 and H2 on the kinetics of cerium hydriding. (12th January 2022) - Fang, Yun; Li, Gan; Li, Haibo; Wu, Min; Wang, Shuaipeng; Bin, Ren; Jiang, Wei; Yao, Yunxi; Luo, Wenhua
Abstract: The reactions of cerium in hydrogen mixed with different concentrations of CO2 were conducted by using a pressure-volume-temperature (PVT) method combined with an in situ hot-stage microscope. CO2 has a great suppression effect on the hydriding reaction of cerium. The existence of CO2 leads to longer induction time, less pitting, and much slower hydriding rate. It is found that the induction time of hydriding reaction grows exponentially as a function of CO2 concentrations. Besides, the nucleation and growth of hydride spots are also suppressed with increase of CO2 concentrations. Scanning electron microscopy (SEM) and in situ optical microscope measurements reveal that the hydride spots formed in H2 -CO2 mixture have a prolate hemispherical morphology while the normal hydride spots formed in pure H2 show an oblate hemispherical morphology. Thermal desorption results indicate CO2 preferentially adsorbs on the active sites of CeO2 surface resulting in block of hydrogen dissociation, which is accountable for the observed hydriding inhibition phenomenon. Our studies provide new insights into the CO2 effect on the hydriding process of active metals. Graphical abstract: Image 1 Highlights: The existence of CO2 in H2 has great suppression effect on cerium hydriding reaction. Adding of CO2 leads to a longer induction time and less pitting density. Adsorption of CO2 on the CeO2 active sites inhibits hydrogen dissociation. Hydride spots show higher protrusion and prolate hemispherical morphology with CO2 .